2019
DOI: 10.1002/btpr.2767
|View full text |Cite
|
Sign up to set email alerts
|

Yellow top (Physaria fendleri) presscake: A novel substrate for butanol production and reduction in environmental pollution

Abstract: Yellow Top (Physaria fendleri) is a plant that belongs to the mustard family. This plant is used to produce seeds that are rich in hydroxy oil. After extraction of oil, the presscake is land filled. The seedcake is rich in polymeric sugars and can be used for various bioconversions. For the present case, the seedcake or presscake was hydrolyzed with dilute (0.50% [v/v]) H 2 SO 4 and enzymes to release sugars including glucose, xylose, galactose, arabinose, and mannose. Then, the hydrolyzate was used to produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…At these YT sugar concentrations, ABE yields ranging from 0.39 to 0.57 were obtained (Table ). A detailed discussion of obtaining high yield has been provided in a previous article . ABE yields obtained in the present studies are similar to our previously reported yields (0.48–0.56) on YT fermentation.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…At these YT sugar concentrations, ABE yields ranging from 0.39 to 0.57 were obtained (Table ). A detailed discussion of obtaining high yield has been provided in a previous article . ABE yields obtained in the present studies are similar to our previously reported yields (0.48–0.56) on YT fermentation.…”
Section: Resultssupporting
confidence: 90%
“…Details of YT, its composition, pretreatment and hydrolysis have been published elsewhere . YT contained 45.1% (w/w) total sugars and 22.4% (w/w) lignin .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations